Autophagy and protein aggregation as a mechanism of dopaminergic degeneration in a primary human dopaminergic neuronal model - Elvis Cuevas; Aida Guzman; Susan M. Burks; Alejandro Ramirez-Lee; Syed F. Ali; Syed Z. Imam (Toxicology Reports, 2022)
The pathophysiology underlying the loss of dopaminergic neurons in Parkinson’s disease (PD) is unclear. A gap of knowledge in the molecular and cellular events leading to degeneration of the nigrostriatal DA system is a major barrier to the development of effective therapies for PD. 1-methyl-4-phenylpyridinium (MPP+) is used as a reliable in vitro model of PD in dopaminergic neurons; however, the molecular mechanisms that lead to cell death with this model are not fully understood. Additionally, there is a lack of translational in vitro models to fully understand progressive dopaminergic neurotoxicity. Here, we propose cultures of primary human dopaminergic neuronal precursor cells (HDNPCs) as a model to study progressive dopaminergic toxicity and neuronal damage in PD. We evaluated the concentration-response of MPP+ (0–10 mM) at 24 h, using cell viability and mitochondrial activity assays (LDH, XTT, Live/Dead staining, and MitoTracker). Based on concentration-response data, we chose two concentrations (1.0 and 2.5 mM) of MPP+ to evaluate markers of autophagy and dopaminergic status [tyrosine hydroxylase (TH)] after a 24-h exposure. Exposure to MPP+ induced cytotoxicity, reduced cell viability, and decreased mitochondrial activity. MPP+ at 1.0 and 2.5 mM also induced expression of lysosome-associated membrane protein 1 (LAMP-1) and increased the ratio of light chain 3 (LC3), LC3BII/LC3BI. The expression of TH also decreased. Furthermore, α-synuclein (α-SYN) and parkin were evaluated by immunofluorescence (IF) at 1.0 and 2.5 mM MPP+ after 24 h. A qualitative analysis revealed decreased parkin expression while α-SYN aggregation was observed in the cytoplasm and the nucleus. These data suggest that in HDNPCs MPP+ can cause cytotoxicity and neuronal damage. This damage may be mediated by autophagy, dopamine synthesis, and protein aggregation. The combination of HDNPCs and MPP+ may serve as valuable in vitro model of progressive dopaminergic neurotoxicity for research into potential treatments for PD.